Investigation of environmental factors impact on fish catch in East Java Waters - Suliskania Nurfitri; Ajeng Tiara Putri; Mutiara Rachmat Putri (Depik, 2025)
This study explores the relationship between environmental parameters and fish catch rates for scad, skipjack, and yellowfin tuna in East Java waters from 2019 to 2022. The environmental factors considered include sea surface temperature (SST), chlorophyll-a concentration, and Ekman pumping velocity (EPV) as indicators of upwelling. SST and chlorophyll-a data were obtained from Aqua MODIS satellite observations, while wind and seawater density data for EPV calculations were sourced from ERA5 and SMOS-OI, respectively. Fish catch data were provided by the Department of Marine and Fisheries of East Java. Cross-correlation analysis revealed a negative correlation between SST and fish catch, with time lags of 2, 4, and 5 months for scad, skipjack, and yellowfin tuna, respectively. Chlorophyll-a concentration showed a positive correlation with fish catch, particularly for scad (0.6 with a one-month lag) and for skipjack and yellowfin tuna (0.62 with a four-month lag). Additionally, EPV exhibited a positive correlation (0.3 to 0.6) with fish catch. These findings emphasize the significance of SST and chlorophyll-a as indicators of fish population dynamics and offer valuable insights for fisheries management.Keywords:East Java WatersSea surface temperatureChlorophyll-aFishcatchUpwelling